Uma nova Rauia (Rutaceae) da Amazônia Brasileira - Rodrigues, William Antônio; Silva, Marlene Freitas da (Acta Amazonica, 1971)
In this paper one new species of RutaceaeRauia prancei is described with one accompaning drawing. This species is distinct from the other by presenting 2 petals with staminodes connected until 2/3 in total lenght and 3 free staminodes and also by anther, disc and stigma shape.